Visi-Misi Ma’ânî al-H?adîth dalam Wacana Studi H?adîth - M. Achwan Baharuddin (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2014)
This papper discusses about Ma’ânî al-H?adîth that offered by contemporary research of h?adîth. The basic issue that discusses of aim Ma’ânî al-Hadîth, how historicity and to be achieved for it. The conclusion from this research is Ma’ânî al-Hadîth of efforts to maintain originally hadith through text matn as viewpoint with many paradigm after known authenticity hadith through repots transmitted sanad. Text hadith, thus, become to doctrinal permanent that must holded on Muslim to be side of life.